ANALYSIS OF WORK SPECIFICATIONS ON LABOR WAGES AT EARLY CHILHOOD SCHOOL IN TRIENGGADENG SUB-DISTRICT, PIDIE JAYA - INDONESIA: A STUDY OF IJĀRAH AL-'AMĀL THEORY - Putri Maisarah, Intan; Sumardi, Dedy; Eriyanti, Nahara (JURISTA: Jurnal Hukum dan Keadilan, 2024)
This study discusses the issue of work specifications and wage provisions which are analyzed using the concept of ijārah al-'amāl. In practice, there is still a discrepancy between the work specifications imposed on workers and wages that are not in accordance with the level of risk and responsibility of workers in early childhood school (Pendidikan Anak Usia Dini [PAUD]). This causes workers' welfare to be neglected and has implications for the quality of services provided. This study is a type of juridical-empirical research using primary and secondary data, primary data obtained through interview techniques and secondary data obtained through reviewing library materials. The data collected was analyzed in qualitative descriptive form which was arranged systematically. The results of the research show that work specifications regarding labor wages at PAUD IT Mahkota Insani, PAUD Kasih Ibu and PAUD RA An Nur are fixed through calculating working days and hours for 6 days a week and working hours of 8 hours per day. Viewed according to the theory of ijārah al-'amāl, even though the terms and conditions of the contract have been fulfilled, there are problems in determining wages that do not fairly consider the level of risk and responsibility of workers in PAUD. To achieve justice and worker welfare in line with maqāṣid al-sharī'ah, it is necessary to make wage adjustments that take into account the number of children handled, the level of risk, and the responsibilities of each worker. In this way, the wages received reflect more justice and provide adequate welfare for workers.